2018
DOI: 10.1021/jacs.7b12773
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Methanol Reaction with OH at Interstellar, Atmospheric, and Combustion Temperatures

Abstract: The OH radical is the most important radical in combustion and in the atmosphere, and methanol is a fuel and antifreeze additive, model biofuel, and trace atmospheric constituent. These reagents are also present in interstellar space. Here we calculate the rate constants, branching ratios, and kinetic isotope effects (KIEs) of the hydrogen abstraction reaction of methanol by OH radical in a broad temperature range of 30-2000 K, covering interstellar space, the atmosphere, and combustion by using the competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
190
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(218 citation statements)
references
References 82 publications
26
190
2
Order By: Relevance
“…Similar behaviour has been observed for other reactions in the solid state. 23,24 There have been several theoretical studies of the OH+methanol reaction 25,26 Figure 6. 8 MESMER is able to reproduce the general shape of the upturn of k3(T) at low temperatures, but was not able to give quantitative agreement.…”
Section: The Reaction Of Oh With Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behaviour has been observed for other reactions in the solid state. 23,24 There have been several theoretical studies of the OH+methanol reaction 25,26 Figure 6. 8 MESMER is able to reproduce the general shape of the upturn of k3(T) at low temperatures, but was not able to give quantitative agreement.…”
Section: The Reaction Of Oh With Methanolmentioning
confidence: 99%
“…8 MESMER is able to reproduce the general shape of the upturn of k3(T) at low temperatures, but was not able to give quantitative agreement. A recent theoretical study also probed the shape of k3 at low temperatures, and found a significant effect of the anharmonicity of high-frequency modes of transition states, and showed that tunnelling led to an unusual negative temperature dependence below 100 K. 25 The rate of tunnelling is expected to decrease dramatically for deuterated methanol, but unfortunately rapid exchange of D with H via the walls of the gas-lines led to the formation of CD3-OH, and any so effect could not be studied experimentally. 8 The spectroscopy and dynamics of weakly-bound complexes between OH and other species have been extensively studied in free-jet expansions 28 and, more recently, following their stabilisation within helium nanodroplets.…”
Section: The Reaction Of Oh With Methanolmentioning
confidence: 99%
“…[214][215][216][217] by several different groups. The reaction was first studied at low temperature by the Leeds group, who measured the rate coefficient by OH LIF at 63 K and 80 K. They found the rate coefficient for the reaction between OH and methanol was almost two orders of magnitude larger at…”
mentioning
confidence: 99%
“…The formed • H and • OH radicals may react with methanol molecules by the following reactions [43][44][45][46][47][48]…”
Section: Water Roles In Ga Plasma Reforming Of Methanolmentioning
confidence: 99%